PENERAPAN KECERDASAN BUATAN DALAM PENDIDIKAN : PELUANG DAN TANTANGAN - Setiawan, Hendra; Jannah, Aisyah Raudhatul (Jurnal Sosio dan Humaniora (SOMA), 2025)
This study explores the opportunities and challenges in the application of AI in education. This study also discusses the problems that accompany its application in educational institutions.Using qualitative methods with a literature study approach. Data was obtained from the latest journals published in 2024 and 2025. Analyzed one by one in depth. The results of the study show that AI has great potential to improve the quality of education through personalization of learning, automation of administrative tasks, and 24-hour academic support. However, the application of AI also faces challenges such as personal bias, privacy, the digital divide, resistance to change, and excessive dependence on technology. The balance between technological advances and human interaction is key to ensuring that AI functions as a supporting tool. Keywords: Artificial Intelligence, Change, Education, Teachers, Students